Case Report: Dislocation Into Vitreous Cavity and Removal of a Posterior Chamber Phakic Intraocular Lens - He, Jingliang; Zhang, Li; Zheng, Fang; Fang, Xiaoyun (Frontiers in Medicine, 2022)
Abstract Purpose: To report a rare case of delayed dislocation of a novel posterior chamber phakic intraocular lens into the vitreous cavity, which was successfully treated by a reformed technique. Case presentation: A 29-year-old female received Ejinn phakic refractory lens (EPRL) implantation to correct her high myopia. Spontaneous dislocation into the vitreous cavity occurred 26-months postoperatively without traumatic history. Pars plana vitrectomy combined with cutting the EPRL into two equal pieces was performed to remove the dislocated EPRL. Conclusion: Dislocation into the vitreous cavity of EPRL can be successfully and easily removed by our reformed technique. Concerns about zonules-related complications preoperatively, intraoperatively, and postoperatively must be raised in the practice of EPRL implantation.